Furred and feathered friends: How attached are zookeepers to the animals in their care?. Issue 2 (18th October 2021) - Melfi, Vicky; Skyner, Lindsay; Birke, Lynda; Ward, Samantha J.; Shaw, Wendy S.; Hosey, Geoff
Abstract: Keeper‐animal relationships (KARs) appear to be important in zoos, since they can enhance the well‐being of both the animals and the keepers, can make animal husbandry easier, but conversely might risk inappropriate habituation of animals and possible risks to the safety of keepers. It is, therefore, important to know more about the variables involved in relationship formation. Here we use a modified version of the Lexington Attachment to Pets Scale (LAPS) to measure the strength of KARs between keepers and animals in their care, both in the zoo and in the home. LAPS questionnaires were completed by 187 keepers in 19 different collections across three countries. LAPS scores for attachment to zoo animals (ZA) were significantly lower than for pet animals (PA). There was no significant difference in ZA scores between different taxa, but there were significant taxon differences between PA scores. There were significant differences in both ZA and PA scores between different collections. Female respondents scored more highly than males for both ZA and PA. Multiple regression revealed that location, gender, and time spent with animals were significant predictors for ZA, while only gender and taxon were significant predictors for PA. It was concluded that PA scores were comparable with those for the general public, and reflected strong attachment of keepers to their pets, while ZA scores, although also reflecting attachment, were influenced by differences in institutional culture. Abstract : Zoo keepers reported a higher level of attachment for their pets compared to the zoo animals in their care, but keeper bonds were not different between species. Interestingly, attachment to animals was significantly different between zoos, suggesting that Zoo Culture influences keeper‐animal relationships (KAR). Research Highlights: Keeper‐animal relationships (KAR, N  = 187 in 19 institutions in the United Kingdom, Australia, and New Zealand) were explored by comparing their attachment to the zoo animals in their care (ZA) and their pets (PA). Scores of ZA and PA were significantly different: keepers reported significantly higher attachment to their pets compared to the animals they cared for in the zoo. ZA scores were higher in women compared to men, but no difference existed between specie ZA scores were significantly different between zoos: a zoo culture appears to exist which impacts how keepers report and/or feel they are attached to the animals they care for in zoos.